A strategy of development based on innovation - Pierre-Olaf Schut (Revue de Géographie Alpine)
Petzl is a company located in the Grenoble region, in the northern French Alps. Its activity is centred on the production of equipment for mountain sports. Today, the company is an eminent international PMI (small and medium-sized industry) in the industry of sports items, carrying a range of products such as frontal lamps, climbing harnesses and mechanical machines securing rope ascents. It used to be a simple family business offering traditionally-made articles for speleology. The present monograph shows the evolution of its activity under the continued management of Paul Petzl. We hypothesize that the latter launched and perpetuated a growth dynamics thanks to the cultivation of the craftsmanship and values inherited from his father’s company: quality design and total dedication to the users’ safety. The development of the company is mainly established on diversifying its production from speleology to skiing, hiking, climbing, and various other mountain sports which became popular along the years. The success of the company expanding market is due to its capacity to innovate and to offer equipments better adapted to the followers’ needs, especially with regard to safety, a value which transcends all practices and which is the highlight of the company’s identity.